Revision of the Micronoctuidae (Lepidoptera: Noctuoidea). Part 1, Taxonomy of the Pollexinae - Fibiger, Michael (Zootaxa, 2007)
This is the first part of a series of papers on the recently described family Micronoctuidae Fibiger, 2005. Part 1 includes the description of a new subfamily (Pollexinae), two new genera (Disca and Pollex), two new subgenera (Bilobiana and Proma), and 72 new species. One new combination is stated. Two previously described species are redescribed.